(untitled) - Drogemoller, Britt Ingrid

Investigation of genetic variation contributing to antipsychotic treatment response in a South African first episode schizophrenia cohort (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.